Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China. (1st February 2023) - Lin, Yu-Chi; Zhang, Zi-Jin; Cao, Meng-Yao; Fan, Mei-Yi; Mozaffar, Ahsan; Yu, Ming-Yuan; Xie, Feng; Zhang, Yan-Lin
Abstract: Atmospheric hazardous volatile organic compounds (HVOCs) have adverse effects on human health. Health risks derived from inhalation of HVOCs have been widely assessed in Chinese cities, however, source-specific health risk analysis has been rarely done. In this work, the five intensive campaigns for monitoring HVOCs concentrations were conducted in Nanjing between July 2018 and May 2020. These datasets were further used to assess the health risks at the receptor site. The result showed that the average HVOCs concentration was 16.7 ± 20.0 ppb with higher levels in the autumn and winter. HVOCs concentrations exhibited diurnal cycles and peaked at the daytime/nighttime rush-traffic hours. By using the observed HVOCs data, the total lifetime cancer risk (LCRT ) and hazard quotient (HQT ) were estimated to be 1.23 × 10 −3 and 2.3, respectively, indicating the significant cancer risk and non-cancer risk at the receptor site. 1, 1, 2, 2-tetrachloroethane (67%) was the major species to cancer risk while 1, 2-dichloropropane (40%) was the dominant compound of non-cancer risk. Positive matrix factorization (PMF) model was used to resolve the source of HVOCs into vehicle emissions (29%), chemical petroleum (19%), solvent usage (17%), biomass burning (12%), coal combustion (10%), liquefied petroleum gas (9%) and fuel evaporation (4%). By combining the health risk assessments and source apportionment results, we finally concluded that solvent usage dominated both cancer risk and non-cancer risk of exposure to HVOCs at the receptor site. Thus, how to make the control measures to reduce HVOCs emissions from solvent usage will be an important issue for decreasing health risks in this polluted city. Graphical abstract: Image 1 Highlights: Significant cancer risk (1.23 × 10 −3 ) and non-cancer risk (2.3) of exposure to HVOCs were found in Nanjing. 1, 1, 2, 2-tetrachloroethane and 1, 2-dichloropropane were the major HVOCs species to health risks in Nanjing, respectively. Solvent usage was the dominant source to 1, 1, 2, 2-tetrachloroethane and 1, 2-dichloropropane in Nanjing. Solvent usage was the main source to health risks in Nanjing.